PENGARUH PENGELUARAN PEMERINTAH DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BANTEN - Saharudin Didu; Nurul Islamiah (Jurnal Ekonomi-Qu, 2017)
ABSTRACTEconomic growth is still the main destination and an important indicator of the success of regional economic development. Banten provincial economic growth rate has fluctuated. The purpose of this study was to determine the development of local government expenditure allocation and assess their effects on economic growth in the area of Banten province. In studying the effect of economic growth analysis conducted jointly with other relevant variables, namely the government expenditure and employment. The data used are secondary data in the form of panel data within a period of nine years from 2003 to 2011. Test analysis is linear regression using the classical assumption, partial test statistic (t-test) with a degree of confidence of 95 % percent. F test and measured by the R2 test (test determinants). Results of this study have used the hypothesis that if the rise in government expenditure will increase economic growth, if the amount of labor up it will increase economic growth. The conclusion that can be drawn in this paper is that the increase in government expenditure would spureconomic growth, therefore, the development expenditure is on target to be realized. The goal is to attract investors to invest their shares in Banten province, due to the increased investment will spur economic growth Banten more appropriate. As a result of the investment that goes right because construction spending targets will be additional output produced or the opening of a new business pitch, so that employment in Banten absorb. The effect can absorb the labor turnover greater capital flows so that economic growth will increase in Banten.Keywords: Economic Growth, Government Expenditure, Labor